SISTEM INFORMASI BURSA KOMODITI PERTANIAN - Mukti, Reza (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractThe Staple food prices in the market continues to soar high, but farmers as food producers always get a low price due to middlemen engtangled. In the present study the authors would like to build an information system that enables the exchange of agricultural commodities into a direct transaction between the farmer and the buyer in a transparent manner that refers to the market price of the local department of agriculture. Agricultural commodity market information system capable of providing a transaction between buyers and farmers with reference to the market price of the local agricultural bureau.Ã‚Â Keywords: commodity exchange system, growers, end buyers.Ã‚Â AbstrakHarga bahan pangan pokok dipasaran terus melambung tinggi, namun petani sebagai produsen bahan pangan selalu mendapatkan harga yang rendah karena terjerat tengkulak. Dalam penelitian kali ini penulis ingin membangun sistem informasi bursa komoditi pertanian yang mungkin menjadi tempat transaksi langsung antara petani dan pembeli akhir secara transparan yang mengacu pada harga pasar dari dinas pertanian setempat. Sistem informasi bursa komoditi pertanian mampu menyediakan tempat bertransaksi antar pembeli serta petani dengan mengacu pada harga pasar dinas pertanian setempat.Ã‚Â Kata kunci : sistem pertukaran komoditi, pertumbuhan, pembeli